Polysaccharides from Lyophyllum decastes reduce obesity by altering gut microbiota and increasing energy expenditure. (1st November 2022) - Wang, Tao; Han, Junjie; Dai, Huanqin; Sun, Jingzu; Ren, Jinwei; Wang, Wenzhao; Qiao, Shanshan; Liu, Chang; Sun, Li; Liu, Shuangjiang; Li, Dianpeng; Wei, Shenglong; et al.
Abstract: Polysaccharides are known to confer protection against obesity via modulation of gut microbiota. To expand our knowledge of mushroom-derived prebiotics, we investigated the structural characteristics and anti-obesity effects of Lyophyllum decastes polysaccharides. Two heteroglycans were purified and characterized. The isolated polysaccharides effectively reduced obesity and the related disorders in the diet-induced obese (DIO) mice. An altered gut microbiota with enrichments of Bacteroides intestinalis and Lactobacillus johnsonii and an increase of secondary bile acids were detected in the polysaccharide-treated mice. Supplementation of B. intestinalis and L. johnsonii prevented the obesity and hyperlipidemia in DIO mice, demonstrating their causal linkage to the efficacy of polysaccharides. An enhancement of energy expenditure in the brown adipose tissues due to up-regulation of the secondary bile acids-activated TGR5 pathway was deduced to be one of the mechanisms underlying the effect of polysaccharides. These results confirmed Lyophyllum decastes -derived polysaccharides as new prebiotics for preventing and treating obesity.